P283 PROGRESSION OF PULMONARY ARTERIAL HYPERTENSION OR LEFT HEART DISEASE? DO EXERCISE!. (18th May 2022) - Baratto, C; Caravita, S; Villella, F; Sganzerla, P; Perego, G; Badano, L; Parati, G
Abstract: An 80–year–old man, diagnosed with idiopathic pulmonary arterial hypertension (PAH) in 2012 and treated with sildenafil, experienced his first hospitalization for heart failure in June 2019. He had several cardiovascular risk factors (overweight, hypertension, diabetes) and comorbidities (ischemic heart disease, and mild chronic obstructive pulmonary disease), whose progression was excluded. Since this event, he complained a progressive deterioration of the exertional dyspnea (NYHA III), with overt signs of fluid overload, right chambers dilation and high NTproBNP (1366 ng/L). However, the center taking care of this patient neither decided to fully re–evaluate him nor to escalate PAH–treatment due to his clinical profile (high suspicion of left heart disease, LHD). He then came to our pulmonary hypertension (PH) center where we decided to perform a cardiac catheterization, which showed the persistence of precapillary PH with high pulmonary vascular resistance, PVR (7.6 WU), low cardiac output, CO (2.2 L/min/m2), high right atrial pressure, RAP (12 mmHg). Pulmonary artery wedge pressure (PAWP) and left ventricular end–diastolic pressure (LVEDP) were at the upper limits of normal (13 mmHg and 16 mmHg, respectively) (Figure 1 ). Based on these "borderline" PAWP values, with an intermediate–high pre–test probability of left heart disease, we performed an exercise test with concomitant gas–exchange analysis on a cycle ergometer in the cath lab (Figure 2 ). Exercise induced a steep increase in pulmonary pressure (TPR 9 WU), unrelated to an exaggerate increase in PAWP or LVEDP (whose peak values reached 20 mmHg, with a PAWP/CO slope <2 mmHg/L/min), but entirely dependent on the precapillary component. Transpulmonary gradient (TPG)/CO slope was high, leading to an absent reduction in PVR (6.4 WU at peak), associated to severe increase in RAP (27 mmHg at peak, RAP/PAWP 1.4) (Figure 3 ). CO reserve was reduced (at peak 3.4 L/min/m2), due to both reduced increase in stroke volume and chronotropic incompetence. Accordingly, functional capacity was moderately–severely reduced (peak oxygen consumption was 8 ml/kg/min, 39% of predicted), with exercise hyperventilation. Once excluded LHD as the responsible of clinical worsening, and in consideration of the high–intermediate risk profile of this patient, we upgraded the PAH–specific therapy by adding macitentan, obtaining a subjective clinical improvement and a 3–years period of clinical stability.